2012
DOI: 10.1002/clc.22039
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, and Quality of Life After Catheter Ablation in Patients With Paroxysmal Atrial Fibrillation

Abstract: Background: Patients with paroxysmal atrial fibrillation (AF) experience impaired quality of life (QoL) and psychological distress. Catheter ablation of AF can markedly improve QoL. However, the effect of catheter ablation of AF on psychological status is unknown. Hypothesis: Depression, anxiety, and QoL improve after catheter ablation in patients with paroxysmal AF. Methods: A total of 166 consecutive patients with symptomatic paroxysmal AF were examined. Eighty-two patients (55 men, mean age 55.9 ± 6.1 y) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
2
26
0
3
Order By: Relevance
“…Catheter ablation is effective for improving depression, anxiety, and QoL in patients with AF 35. Similarly, our results showed that depression, anxiety and poor QoL were improved 6 months after RFCA.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Catheter ablation is effective for improving depression, anxiety, and QoL in patients with AF 35. Similarly, our results showed that depression, anxiety and poor QoL were improved 6 months after RFCA.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, all patients included in this study were treated with catheter-based ablation therapy, which contributed to the homogeneity of our sample. However, according to current guidelines for the AF, ablation therapy is recommended as the secondary treatment for patients who are not able to tolerate drugs or who fail the first-line treatment 3435. Thus, the clinical characteristics of our sample may be attributable to the dissociation between personality type and the recurrence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that catheter ablation was effective in reducing symptoms of depression and anxiety and improving quality of life, and it was superior to antiarrhythmic drug therapy [35]. …”
Section: Resultsmentioning
confidence: 99%
“…19 Sang et al demonstrated that contributors to the improvement of depression, anxiety, and QoL included catheter ablation, avoidance of warfarin use, initial higher levels of depression and anxiety, and lower QoL. 20 Outpatients undergoing warfarin therapy had a significantly higher risk for death if they were burdened with symptoms of depression or anxiety showed in a very recent study. 21 Previous data have been conflicting on whether a positive impact on QoL from oral anticoagulant therapy or high levels of displeasure with OAC therapy perhaps associated with poor therapeutic control.…”
Section: Discussionmentioning
confidence: 97%